The Concept of a Hybrid Traction Power Supply System - Sychenko, Viktor G.; Kuznetsov, Valeriy; Kosariev, Yevhen; Bekh, Petro V.; Sayenko, Yuriy; Styslo, Bohdan O.; Pavlichenko, Mihail; Vasilev, Ihor; Pulin, Mykola M. (Les Ulis: EDP Sciences-Web of Conferences, France, 2019)
ENG: Abstract. The growing shortage of energy resources to provide heavy traffic and high-speed traffic necessitates the development of a new power supply scheme for a traction network using sources of distributed generation of electric energy. Application of asymmetric distributed traction power system with the use of distributed generation allows to increase electric energy efficiency of the feed system of rolling stock, reduce its material capacity and increase the reliability of the functioning of the railway system as a whole. The proposed structure of the hybrid electric traction system involves the creation of a new paradigm aimed at ensuring high demands on the voltage and specific power in the traction network, which will allow to improve the quality and safety of the transportation process when increasing the energy performance indicators. This paradigm will allow to form a new philosophy of building traction power systems. The key elements of this philosophy are decentralization of generation and consumption of electric energy, the use of intelligent electric equipment, distributed power supply management in a single information space of the energy process during transportation. The peculiarity of the proposed work is the optimal combination of technological processes of transmission, consumption of electric energy and transportation, taking into account the specific conditions of functioning of the electrified section: points of connection of power sources and their type, profile of the track, schedule of trains, types of rolling stock and equipment. Conceptually, the hybrid traction power system is an electric hub, in which the inputs are generating points, and the output is the power supply system of the rolling stock. The internal structure of the electric power objects of the hub is determined by the type of transformation and accumulation of electric energy and ways of managing these objects in real time.
V. Sychenko: ORCID: 0000-0002-9533-2897; V. Kuznetsov: ORCID 0000-0003-4165-1056; P. Beh: ORCID 0000-0002-1782-9224; Y. Sayenko: ORCID: 0000-0001-9729-4700; B. Styslo: ORCID 0000-0001-7057-3523; M. Pulin: ORCID 0000-0003-0929-671X
Keywords: hybrid power supply system; electrical energy; power traction systems; electrical knot; КІСЕ; КУЕР